Przemoc seksualna w konfliktach zbrojnych - Domagała, Arkadiusz (OTO Agencja Reklamowa, 2014)
The paper presents the position of international governmental organisations in regard to sexual violence in armed conflicts. After civil wars in Bosnia and Hercegovina and Rwanda international society recognizes that conflict – related sexual violence (CRSV) could be considered as genocide or crimes against humanity and treated as a serious threat to international peace and security. Consequently, it is emphasized that prevention of sexual violence in conflicts and gender mainstreaming must be implemented. The advocate of such perspective are the United Nations that creates the conceptual framework for the fight against CRSV through resolutions of Women, Peace, and Security. Actions of other intentionally established agencies within the UN are noticed as well. International organizations differ when implementing the UN guidelines. The EU and NATO are proponents of the systematic protection of women during and after armed conflicts; however, most of organizations remain passive. The latter do not appreciate the issue of sexual violence or do not have adequately properly prepared infrastructure, finance, know – how and primarily human resources. Finally, the paper depicts the specific activities within the peacekeeping operations in the context of combating and prevention of CRSV.
Keywords: organizacje międzynarodowe; politologia; prawa człowieka; demokracja; pomoc humanitarna; migracje; patologie; bezpieczeństwo; terroryzm międzynarodowy; ochrona środowiska